\[\boxed{\text{1030\ (1030).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[x + y = a - 1\]
\[ax + x + ay + y + 1 = a^{2}\]
\[ax + x + ay + y + 1 =\]
\[= a \cdot (x + y) + (x + y) + 1 =\]
\[= (x + y)(a + 1) + 1,\]
\[так\ как\ x + y = a - 1,\ то\ \]
\[(a - 1)(a + 1) + 1 =\]
\[= a^{2} - 1 + 1 = a^{2}\]
\[Что\ и\ требовалось\ доказать.\ \]
\[\boxed{\text{1030.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[y = 4 - x^{2};\ \ \ \ \ \ - 3 \leq x \leq 2\]
\[1)\]
\[x\] | \[- 3\] | \[- 2\] | \[- 1\] | \[0\] | \[1\] | \[2\] |
---|---|---|---|---|---|---|
\[y\] | \[- 5\] | \[0\] | \[3\] | \[4\] | \[3\] | \[0\] |
\[2)\]
\[3)\ y < 0\ \ при\ - 3 \leq x < - 2;\]
\[y > 0\ \ \ при\ \ \ - 2 < x < 2;\]
\[4)\ область\ значений\ :\]
\[- 5 \leq y \leq 4.\]